Epidemiology and classification for canine and feline mammary gland tumors: a histopathological survey of 437 mammary gland tumor biopsies performed in a secondary care hospital in Chiang Mai, Thailand from 2012 to 2019 - Wanwisa Srisawat; Kidsadagon Pringproa; Worapat Prachasilchai; Atigan Thongtharb; Nattawooti Sthitmatee (PeerJ, 2024)
Background Metastatic disease resulting from mammary gland tumors (MGTs) is a known cause of death among dogs and cats. Keys to successful prevention and management strategies involve the accurate recording of diagnostic data. Methods This retrospective study reviewed the epidemiology and classification of canine mammary gland tumors (CMTs) and feline mammary gland tumors (FMTs), as well as the factors including sex, age, and breed related to the occurrence of these tumors. Accordingly, 1,736 tumor biopsy cases were reported from 2012 to 2019 at Chiang Mai University Small Animal Hospital, Thailand, with 1,639 canine tumor biopsy cases and 97 feline tumor biopsy cases. Results The proportion of CMTs was reported at 24.5% (401/1,639) for all canine tumor biopsy cases. Benign and malignant tumors were reported at 14.5% (58/401) and 85.5% (343/401) for all CMT cases, respectively. The mean age of dogs affected by benign CMTs was 9.0 ± 3.0 years, which was significantly lower than for malignant CMTs at 9.9 ± 2.8 years (P = 0.0239). According to histopathological classification, benign mixed tumors and simple carcinoma types were highest among benign and malignant CMT cases, respectively. Moreover, female dogs were at significantly higher risk of developing mammary gland tumors (OR = 45.8, 95% CI [3.9–86.0], P < 0.0001) than male dogs, as well as older dogs (>8 years) (OR = 1.7, 95% CI [1.2–2.2], P = 0.0001) compared to young ones (≤8 years). The proportion of FMTs was 37.1% (36/97) for all feline tumor biopsy cases. Benign and malignant tumors for all FMTs were reported at 16.7% (6/36) and 83.3% (30/36), respectively. According to histopathological classifications, adenoma and simple carcinoma were present in the highest proportion among benign and malignant FMTs, respectively. Female cats were at a significantly higher risk of developing mammary gland tumors than male cats (OR = 25.7, 95% CI [3.9–272.8], P < 0.0001). Conclusions and clinical importance There was a high proportion of MGT cases compared with other tumor cases reported in a secondary care hospital in Chiang Mai, Thailand from 2012 to 2019, and malignant tumor biopsies have been more frequently observed than benign tumor biopsies in both CMT and FMT cases. The resulting data originating from this study can be an aid for veterinary oncologists in better educating clients and planning treatment and prevention strategies and it can be used as a basis for further experimental studies in the oncology section.